TYPOLOGY OF EXERCISES ON THE USE OF COUNTING RHYMES IN GERMAN, ENGLISH AND UZBEK LANGUAGES - Komilova Khabibakhon Zafarbek kizi; Gavxaroy Isroiljon qizi (Journal of new century innovations, 2023)
Abstract: this article presents a typology of exercises that use counting rhymes in German, English, and Uzbek languages. The authors analyze the linguistic and pedagogical aspects of these exercises, highlighting their potential benefits for language learners. Through a comparative analysis of the three languages, the authors identify similarities and differences in the use of counting rhymes as a language learning tool. The article concludes with practical recommendations for teachers and learners who wish to incorporate counting rhymes into their language learning activities.